Defective Wound-healing in Aging Gingival Tissue. (July 2014) - Cáceres, M.; Oyarzun, A.; Smith, P.C.
Aging may negatively affect gingival wound-healing. However, little is known about the mechanisms underlying this phenomenon. The present study examined the cellular responses associated with gingival wound-healing in aging. Primary cultures of human gingival fibroblasts were obtained from healthy young and aged donors for the analysis of cell proliferation, cell invasion, myofibroblastic differentiation, and collagen gel remodeling. Serum from young and old rats was used to stimulate cell migration. Gingival repair was evaluated in Sprague-Dawley rats of different ages. Data were analyzed by the Mann-Whitney and Kruskal-Wallis tests, with a p value of .05. Fibroblasts from aged donors showed a significant decrease in cell proliferation, migration, Rac activation, and collagen remodeling when compared with young fibroblasts. Serum from young rats induced higher cell migration when compared with serum from old rats. After TGF-beta1 stimulation, both young and old fibroblasts demonstrated increased levels of alpha-SMA. However, alpha-SMA was incorporated into actin stress fibers in young but not in old fibroblasts. After 7 days of repair, a significant delay in gingival wound-healing was observed in old rats. The present study suggests that cell migration, myofibroblastic differentiation, collagen gel remodeling, and proliferation are decreased in aged fibroblasts. In addition, altered cell migration in wound-healing may be attributable not only to cellular defects but also to changes in serum factors associated with the senescence process.